A framework for assessing social structure in community governance of sustainable urban drainage systems: insights from a literature review - Simon Peter Muwafu; Lena Rölfer; Jürgen Scheffran; María Má\~nez Costa (Mitigation and Adaptation Strategies for Global Change, 2024)
The utilization of Sustainable Urban Drainage Systems (SUDS) as Nature-based Solutions (NBS) holds significant promise for enhancing resilience against climate change-induced flooding and promoting community well-being in urban areas of Sub-Saharan Africa. While existing research predominantly emphasizes technical aspects within the NBS framework, understanding the socio-governance dynamics at the community level is equally imperative, particularly given the decentralized nature of SUDS. This study aims to complement the prevailing technical focus by examining the social dimensions of community governance related to SUDS implementation. Through a literature review, key determinants of social structure influencing successful community governance in SUDS management are identified, and categorized into actors, resources, discourses, and rules of engagement. An innovative assessment framework comprising 65 indicators is proposed to evaluate these determinants, offering a comprehensive tool for scholars and practitioners. By integrating social considerations into SUDS management practices, this research seeks to inform policy formulation and strategies tailored to Sub-Saharan African cities, facilitating equitable and participatory urban stormwater management initiatives crucial for addressing climate change challenges.
Keywords: 330; Urban Stormwater Management; Green Infrastructure; Sub-Saharan Cities; Adaptation; Policy Arrangement Approach; Literature review